Lower urinary tract obstruction secondary to -associated struvite urolithiasis in a female cat - Dennis J Woerde; Carrie A Palm; Emily C Cutolo; Helen S Philp; Jodi L Westropp (Journal of Feline Medicine and Surgery Open Reports)
Case summary A 10-year-old female neutered domestic shorthair cat presented with stranguria. The cat was bradycardic and had a firm urinary bladder on physical examination. On initial laboratory testing, the cat had severe azotemia with a creatinine of 15.8 mg/dl (reference interval [RI] 1.1–2.2), blood urea nitrogen of 217 mg/dl (RI 18–33) and potassium of 8.9 mmol/l (RI 3.5–5.0). Abdominal radiography revealed three cystoliths, with one cystolith suspected of being lodged within the trigone. Ultrasound of the abdomen showed marked suspended echogenic debris within the urinary bladder. Corynebacterium urealyticum was isolated from aerobic bacterial urine culture. A cystotomy was performed, and crystallographic analysis of the removed cystoliths showed they were composed of 94% struvite and 6% calcium phosphate. The cat recovered well and was discharged 2 days postoperatively. Three weeks postoperatively, the cat showed resolution of all clinical signs and azotemia. Relevance and novel information Urethral obstruction is common in male cats because of the narrow diameter of their urethra. In contrast, it is rare for female cats to experience lower urinary tract obstruction (LUTO). Identifying the underlying cause of LUTO is crucial for providing appropriate and targeted treatment. This case report describes a unique cause of LUTO resulting from C urealyticum associated with struvite urolithiasis in a female cat.